Globalizing Roman culture : unity, diversity and empire - Hingley, Richard (London ; New York : Routledge, 2005)
A study of identity and social change in the Roman empire and the relationship of this knowledge to understanding of the contemporary world.
Chapter 1 THE PAST IN THE PRESENT -- chapter 2 CHANGING CONCEPTS OF ROMAN IDENTITY AND SOCIAL CHANGE -- chapter 3 ROMAN IMPERIALISM AND CULTURE -- chapter 4 THE MATERIAL ELEMENTS OF ELITE CULTURE -- chapter 5 FRAGMENTING IDENTITIES -- chapter 6 'BACK TO THE FUTURE'? Empire and Rome.
Includes bibliographical references (pages 162-194) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Rome -- Civilization -- Influence; Acculturation -- Rome; Rome -- Civilisation -- Influence; Éducation au développement -- Rome; HISTORY -- Ancient; Acculturation; Civilization -- Influence; Rome (Empire)